Tear production, intraocular pressure, and conjunctival bacterial flora in a group of captive black‐tailed prairie dogs (Cynomys ludovicianus). (15th October 2014) - Meekins, Jessica M.; Eshar, David; Rankin, Amy J.
Abstract: Objective: To report ocular diagnostic test parameters and normal conjunctival bacterial flora in captive black‐tailed prairie dogs. Animals studied: Seventeen black‐tailed prairie dogs, ranging in age from approximately 4–6 months to 4.5 years. Eleven males came from a zoo collection and 6 females from a wildlife rehabilitation center. Procedures: Complete ocular examination was performed under isoflurane anesthesia. Tear and intraocular pressure (IOP) measurements were performed on both ( n = 34) eyes of 17 prairie dogs. Phenol red thread test (PRTT) was performed first, and a modified Schirmer tear test I (mSTTI) was performed 10 min later. Indirect rebound tonometry was performed using the TonoVet ® . Attempts to obtain intraocular pressure measurements using an applanation tonometry instrument were unsuccessful. Conjunctival swab samples ( n = 17) were taken from both eyes of each prairie dog and pooled. Results: The most common ocular abnormality was acquired eyelid margin defects, present in seven eyes of six prairie dogs (35.3%). Mean ± SD tear production was 13.6 ± 7.8 mm/15 s (range, 3–30) for PRTT and 1.2 ± 0.9 mm/min (range, 0–4) for mSTTI. Mean ± SD IOP was 7.7 ± 2.2 mmHg (range, 3–11.4). A Staphylococcus xylosus (7/17; 41.2%) organism and a hemolytic Staphylococcus species (5/17; 29.4%) were most commonly isolated from the prairie dog conjunctival sac. Conclusions: There was a moderate prevalence of acquired peri‐ocular lesions in this group of captive black‐tailed prairie dogs. While widely variable, results of tear test and intraocular pressure measurements are reported. Staphylococcus was the most commonly isolated bacterial genus.